Atmospheric corrosion maps as a tool for designing and maintaining building materials: A review (2022)
Atmospheric corrosion maps can be used to conduct a fast and graphical assessment of material deterioration in specific geographic environments. These maps are a key tool for selecting the most adequate materials in terms of corrosion resistance, maintenance, and cost-efficiency in outdoor constructions. Several studies have evaluated the effects of environmental factors and pollutants on building materials at local, regional, national, and international levels. However, not enough atmospheric corrosion maps are readily available, possibly due to thecomplexity of the variables that should be considered to construct them, which include weather, meteorological,and pollution-related factors that vary in space and time. This article presents a thorough literature review of atmospheric corrosion maps published between 1971 and 2021 mainly indexed in the Scopus database. It is complemented with a detailed review of books, journals, and projects by research centers that focuses on the methodologies, parameters, and tools that have been used to construct said maps. Most of the available maps are outdated, which highlights the need for new maps that reflect recent global changes in atmospheric pollution and temperature that can intensify metal deterioration in some places.